FAST FOOD GENERATION: THE RELATIONSHIP BETWEEN JUNK FOOD CONSUMPTION DUE TO NON-COMPLIANCE AND THE SURGE IN CHILDHOOD DIABETES CASES IN URBAN AREAS - Hutapea, Dwight Mahaputera Marulitua (MSJ : Majority Science Journal, 2025)
Rapid urbanization in Indonesia's urban areas has changed children's food consumption patterns, shifting from fresh and home-cooked foods to junk foods high in calories, saturated fat, sugar, and sodium. This change is driven by easy access, economic dynamics, and exposure to media and massive marketing, which shape food preferences from an early age. A food environment dominated by junk food narrows opportunities for healthy food consumption, while the busy urban pace of life encourages families to choose fast food as a practical solution. Socioeconomic factors influence the type and frequency of consumption, but dependence on junk food occurs across all levels of society. Low parental nutritional literacy, minimal promotional regulations, and the dominance of digital marketing reinforce this trend. Consequently, the risk of obesity and type 2 diabetes in children has increased significantly, exacerbated by a sedentary lifestyle and low physical activity. Physiologically, a diet high in sugar and trans fats triggers insulin resistance, chronic inflammation, and pancreatic β-cell fatigue. This phenomenon demands evidence-based, multidimensional interventions that include marketing regulations, food environment management, school-based nutrition education, and strengthening the role of families. Cross-sector collaboration and a continuous evaluation system are needed to simultaneously change socio-environmental determinants, so as to suppress the rate of the metabolic disease epidemic in urban youth.